Psychotropic dose equivalence in Japan - Inada, Toshiya; Inagaki, Ataru (Psychiatry and clinical neurosciences, 2015)
Psychotropic dose equivalence is an important concept when estimating the approximate psychotropic doses patients receive, and deciding on the approximate titration dose when switching from one psychotropic agent to another. It is also useful from a research viewpoint when defining and extracting specific subgroups of subjects. Unification of various agents into a single standard agent facilitates easier analytical comparisons. On the basis of differences in psychopharmacological prescription features, those of available psychotropic agents and their approved doses, and racial differences between Japan and other countries, psychotropic dose equivalency tables designed specifically for Japanese patients have been widely used in Japan since 1998. Here we introduce dose equivalency tables for: (i) antipsychotics; (ii) antiparkinsonian agents; (iii) antidepressants; and (iv) anxiolytics, sedatives and hypnotics available in Japan. Equivalent doses for the therapeutic effects of individual psychotropic compounds were determined principally on the basis of randomized controlled trials conducted in Japan and consensus among dose equivalency tables reported previously by psychopharmacological experts. As these tables are intended to merely suggest approximate standard values, physicians should use them with discretion. Updated information of psychotropic dose equivalence in Japan is available at http://www.jsprs.org/en/equivalence.tables/. [Correction added on 8 July 2015, after first online publication: A link to the updated information has been added.]